Modulation of inflammation and endothelial activation with spaceflight travel: tocotrienols as atheroprotective agents / Suhaila Abd Muid - Abd Muid, Suhaila (Institute of Graduate Studies, UiTM, 2014)
The effects of immediate spaceflight travel on inflammation and endothelial activation in human endothelial cells (ECs) is not yet established. In addition, the expression of these biomarkers in revived live ECs recovered from a spaceflight travel has not been reported so far. Endothelial activation is preventable. One of the major preventive strategies is the usage of antioxidants. Tocotrienols (TCTs) is a more potent antioxidant than tocopherol (TOC). However, the role of Tocotrienol enriched mixed fraction (TEMF) and pure TCT isomers as a potential potent antiatherosclerotic agent in human ECs compared to pure α-TOC is not well established.